The Determinants of the Use of Cloud-Based Regional Management Information Systems: an Approach Using Dual Factor Theory - Putri, Nindia Nur Arifiana; Rosidi, Rosidi (Journal Research of Social Science, Economics, and Management, 2026)
The purpose of this study is to investigate enablers and inhibitors including the dual factor theory of the use of cloud-based regional management information systems. Sampling in this study used the purposive sample technique. The software used in this study is SmartPLS 2. The results show that first, IT infrastructure problems have a negative effect on the perception of usability. Second, IT infrastructure problems have a negative effect on the perception of ease of use. Third, IT infrastructure problems have a negative effect on the use of cloud-based regional information systems. Fourth, the problem of human resource competence has a negative effect on the perception of usability. Fifth, the problem of human resource competence has a negative effect on the perception of ease of use. Sixth, the problem of human resource competence has a negative effect on the use of cloud-based regional information systems. Seventh, the perception of usability has a positive effect on the use of cloud-based regional information systems. Eighth, the perception of ease of use has a positive effect on the use of cloud-based regional information systems.